Price transparency reflects assurance and reliability. (July 2016) - Mittal, Divya; Agrawal, Shiv Ratan
Abstract: This paper aims to examine the effect of price transparency on assurance, reliability and customer loyalty in the case of Wal-Mart Best Price Store. A total of 402 usable responses were gathered from customers of Wal-Mart store in Bhopal (MP), India. The study scales were refined and validated by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The AMOS 22.0 and SmartPLS 3.0 statistical programmes were used for measurement validation and to test the structural model. The results indicated that the price transparency has a significant effect on assurance and reliability to ensure customer loyalty. Also, the study did not find a direct effect of price transparency on customer loyalty. The identified dimensions of price transparency are expected to bring clarity to the issue of customer assurance, reliability and loyalty. This would help the management of the retailing sector. The study seems to offer opportunities to understand that only price transparency is not responsible for improving customer loyalty. It influences assurance and reliability which further increase customer loyalty. Highlights: The results indicated that the price transparency has a significant effect on assurance and reliability to ensure customer loyalty. The study seems to offer opportunities to understand that only price transparency is not responsible for improving customer loyalty. It influences assurance and reliability which further increase customer loyalty. This would help the management of the retailing sector.